PEMANFAATAN SIFAT OPTIS AKTIF ALAMI UNTUK KENDALI MUTU MINYAK GORENG MENGGUNAKAN LAMPU PIJAR - Asy Syifa, A Y; Nisa, Fathia; Prasanti, Irvani D; Murni, Sri; Firdausi, K Sofjan (BERKALA FISIKA, 2013)
In this study the properties of natural optical activity of the various vegetable cookingoils was used as a new method for a quality control and was proposed as a new prospect forpreliminary test of oil quality. The samples used were various packaging cooking oil obtained inthe shops and were considered already fulfilled by SNI. The source of light to illuminate was a75W light-bulb. The change of the polarization angle of light was measured using polarizer basedon Malus’ law, and it was used to indicate the levels of oil quality degradation. The experimentalresult shows that highest change of polarization angle indicates relative lowest quality of oils. Anolive oil shows the best oils relative from other types of vegetable oils. The natural polarization inthis case is able to differentiate between various types of oil, and to distinguish fresh oil andexpired oil. It seems that natural polarization accommodates some contributed components oflevel of degradation of oil quality, i.e. free fatty acid and saturated fat. This method provides someadvantages, such as, simple equipments, a fast test, without preliminary treatment, and accurateresults. For the future, it shows a reliable test to conduct as a previous quality control for cookingoil and replaces the role of conventional, expensive standard methods. This method offers also achallenge to evaluate the level of authentication or halal of oils and fats.Keywords: oil quality, polarization angle, optical activity.